Empowering Gampoeng Sungai Pauh Firdaus Women through Sirih Art Training: Sustainable Tradition Rezeki Approaches - Nanda Safarida (Jurnal Pengabdian Masyarakat Bestari, 2022)
The implementation of community service activities through empowering women in Gampoeng Sungai Pauh Firdaus with Sirih Stringing Art Training aims to provide an understanding of the physical benefits of betel and improve skills in arranging decorative/creative betel leaves for use in various traditional events. The service method is carried out by means of observation, discussion, demonstration and direct practice through three stages namely planning, implementation and evaluation. The results of this activity are expected to be able to add insight, understanding and skills to women in Gampong. So as to be able to take a role in preserving Aceh's cultural customs and maintaining one of Aceh's local wisdom. In addition, with the skills possessed by women, it is hoped that they will be able to have economic independence which will then have an impact on social welfare.